A case report of myxoma within the right submandibular muscle and a literature review - Tian, Dingyu; Liang, Xiao; Ma, Juntao; Li, Ye; Zhang, Yuliang; Zhang, Rui (Frontiers in Surgery, 2026)
ObjectiveTo investigate the etiology, clinical presentation, management, and prognosis of intramuscular myxoma occurring in the submandibular region.MethodsA case of intramuscular myxoma originating from the mylohyoid muscle was analyzed. The patient's clinical history, imaging features, surgical findings, and pathological results were reviewed. Relevant characteristics were summarized in the context of previously published literature.ResultsThe patient presented with a painless mass in the submandibular area. Computed tomography revealed a cystic lesion, and postoperative histopathological examination confirmed the diagnosis of intramuscular myxoma. The patient recovered well following surgical excision.ConclusionIntramuscular myxoma is a rare benign soft-tissue tumor, with an estimated incidence of approximately 0.10–0.13 per 100,000 individuals. Lesions arising in the submandibular muscles are exceptionally uncommon and may be misdiagnosed as sublingual gland cysts. Due to the nonspecific clinical manifestations and potential for misdiagnosis on imaging, histopathological evaluation remains the definitive diagnostic method. Complete surgical excision is the treatment of choice and is generally associated with a favorable prognosis.